2021
DOI: 10.26434/chemrxiv.13308875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Common Ground of Thermodynamics and Kinetics: How to Pin Down Overpotential to Reversible Metal Hydride Formation and the Complete Ideal Gas Theory of Reversible Chemical Hydrogen Storage

Abstract: Ti-doped NaAlH<sub>4</sub> requires at 125 °C for [AlH<sub>4</sub>] formation more than twice the equilibrium pressure; while it is straightforward to relate this conditional surplus in hydrogenation pressure respective chemical potential to kinetic hindrance, it appears strange that this matter has not been duly theoretically addressed in literature to this day. The interest in identifying such overpotentials is not of purely academic interest but touches a problem of very practical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…15 Second, the van't Hoff reaction parameter H and S need to be precisely assessed. 16 Third, on that data basis the kinetic hindrance to the reaction may be expressed in terms of chemical overpotential; 17 this free enthalpy leads via an Eyring-Polyani approach to a non-experiment specific k 0,EP value. 18 Fourth, on basis of these two objective Arrhenius parameters, factor y may be modelled for a specific experiment.…”
Section: Resultsmentioning
confidence: 99%
“…15 Second, the van't Hoff reaction parameter H and S need to be precisely assessed. 16 Third, on that data basis the kinetic hindrance to the reaction may be expressed in terms of chemical overpotential; 17 this free enthalpy leads via an Eyring-Polyani approach to a non-experiment specific k 0,EP value. 18 Fourth, on basis of these two objective Arrhenius parameters, factor y may be modelled for a specific experiment.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions are not particularly new, SANDROCK et al reported them already in 2002, 17 yet that formation overpotential issue was never duly recognized in literature until the author clarified it's nature on basis of fundamental kinetic and thermodynamic reaction parameters. 18 Thus, the problem is already solved with general significance by an approach from the system's gas phase end but the flipside effect must be recognizable in a particular sorbent as well, though in terms of molar volume than pressure and temperature. Towards that end, equation 6 is transformed for p° and inserted into the van't Hoff equation with subsequent transformations as shown in equations 8a to 8d.…”
Section: - Mhmentioning
confidence: 99%
“…⇒ V m,NaAlH4 = 42.52 cm 3 mol -1 ≈ 43 cm 3 mol -1 (12a) The result of 78.5 bar in equation 14c for the minimum hydrogenation pressure is in excellent agreement with the old empiric value of about 79 bar, 17 respective the result obtained from the gas phase-centred approach of 78.7 bar. 18 It is noteworthy that approaching the issue from the gas phase perspective requires further knowledge of the activation energy but focussing on molar volume in the sorbent phase encloses that information in blanket fashion: yet the gas phase approach offers more insight as yielding not only the threshold pressure but also the threshold temperature to hydride phase formation. 18 A final point is made about why a pressure considerably above the [ The realization that only the argumentative switch towards the gas phase allows the eventual conclusion of an issue which is allegedly entirely sorbent-phase related is a matter of essence.…”
Section: - Mhmentioning
confidence: 99%
“…M NaAlH4 = 54 g mol -1  NaAlH4 = 1.27 g cm -3 ⇒ V m,NaAlH4 = 42.52 cm 3 mol -1 ≈ 43 cm 3 mol -1 (12a) The result of 78.5 bar in equation 14c for the minimum hydrogenation pressure is in excellent agreement with the old empiric value of about 79 bar, 17 respective the result obtained from the gas phase-centred approach of 78.7 bar. 18 It is noteworthy that approaching the issue from the gas phase perspective requires further knowledge of the activation energy but focussing on molar volume in the sorbent phase encloses that information in blanket fashion: yet the gas phase approach offers more insight as yielding not only the threshold pressure but also the threshold temperature to hydride phase formation. 18 A final point is made about why a pressure considerably above the The realization that only the argumentative switch towards the gas phase allows the eventual conclusion of an issue which is allegedly entirely sorbent-phase related is a matter of essence.…”
mentioning
confidence: 99%
“…18 It is noteworthy that approaching the issue from the gas phase perspective requires further knowledge of the activation energy but focussing on molar volume in the sorbent phase encloses that information in blanket fashion: yet the gas phase approach offers more insight as yielding not only the threshold pressure but also the threshold temperature to hydride phase formation. 18 A final point is made about why a pressure considerably above the The realization that only the argumentative switch towards the gas phase allows the eventual conclusion of an issue which is allegedly entirely sorbent-phase related is a matter of essence. This refutes a narrow positivist understanding of the problem, emphasizing an exclusive sorbent phase bias of tangibles: declaring the essential non-essential breaches causality and must preclude convergence in outcome and insight alike.…”
mentioning
confidence: 99%